Effects of pressure, methane concentration, sulfate reduction activity, and temperature on methane production in surface sediments of the Gulf of Mexico. (25th June 2018) - Zhuang, Guang‐Chao; Montgomery, Andy; Sibert, Ryan J.; Rogener, Mary‐Katherine; Samarkin, Vladimir A.; Joye, Samantha B.
Abstract: Microbial methanogenesis is a known source of methane in marine environment, but the factors affecting the production of methane from different pathways remain largely unconstrained. We investigated the effects of pressure, methane concentration, temperature, and sulfate reduction activity on the conversion of methanogenic substrates to methane using radiotracers in nearshore and offshore surface sediments in the northern Gulf of Mexico. The transformation of bicarbonate to methane increased with methane concentrations under quasi in situ conditions of deep‐sea sediment, potentially reflecting, to some degree, enhancement of the enzymatic back reaction under high‐methane conditions. In coastal sediments, a positive effect of both increased methane concentration and inhibition of sulfate reduction by molybdate on 14 CH4 accumulation suggests that anaerobic oxidation of methane and methanogenesis occur concurrently. In contrast, methane production from methanol was suppressed by increased methane concentration likely due to the reduced energy yield of methanogenesis at elevated methane concentrations. Temperature could limit hydrogenotrophic and acetoclastic methanogenesis under in situ conditions, as higher rates were observed at 40°C in nearshore sediments. Inhibitor experiments with 2‐bromoethanesulfonate and molybdate indicated that sulfate‐reducing bacteria preferentially utilized acetate, as well as H2 . Methanol was a noncompetitive substrate for methanogens in the deep‐sea sediments but was competitively cycled in coastal sediments. An authentic noncompetitive substrate, methylamine, was channeled predominantly to methane production under all conditions tested. The different response of methanogenic activity to substrate availability, metabolic competition, temperature, and pressure between sites suggest variable environmental controls on the methane production in coastal vs. deep‐sea surface sediments.